Relation between plasma trough concentration of abiraterone and prostate-specific antigen response in metastatic castration-resistant prostate cancer patients. (February 2017) - Carton, E.; Noe, G.; Huillard, O.; Golmard, L.; Giroux, J.; Cessot, A.; Saidu, N.E.B.; Peyromaure, M.; Zerbib, M.; Narjoz, C.; Guibourdenche, J.; Thomas, A.; et al.
Abstract: Background: Abiraterone (ABI) is a major oral agent for the treatment of metastatic castration-resistant prostate cancer (mCRPC) patients but its systemic exposure is subject to a large inter-individual variability. We aimed to explore the relationship between ABI trough plasma concentration and prostate-specific antigen (PSA) response in mCRPC patients and to identify the critical determinants for its activity. Patients and methods: This is a monocentric prospective observational study in mCRPC patients treated with ABI. The plasmatic concentration of ABI at steady state was measured using liquid chromatography with fluorescence detection. The primary objective was to study the relationship between mean ABI plasma exposure (ABI Cmin ) and 3-month PSA response. Results: From 2012 to 2016, 61 mCRPC patients were eligible for pharmacokinetic/pharmacodynamic assessment. Thirty-eight patients experienced PSA response (62%, [confidence interval CI 95% 50–78]). In univariate analysis, ABI Cmin was 1.5-fold higher in responders: 12.0 ng/mL (CI 95% 9.4–15.6) versus 8.0 ng/mL (CI 95% 5.8–11.6; P = 0.0015). In multivariate analysis, only ABI Cmin was independently associated with PSA response (odds ratio = 1.12 [CI 95% 1.01–1.25], P = 0.004). By receiver operating characteristic analysis, the optimal threshold for ABI Cmin was 8.4 ng/mL. Progression-free survival (PFS) was significantly higher in patients with ABI Cmin above 8.4 ng/mL (hazard ratio 0.55, [CI 95% 0.31–0.99], 12.2 [CI 95% 9.2–19.5] versus 7.4 [CI 95% 5.5–14.7] months otherwise, P = 0.044). Conclusions: We showed that ABI trough concentration correlates with PSA response and PFS. Moreover, we could determine a cut-off value of plasmatic concentration for PSA response. Altogether, ABI concentration monitoring appears as a new approach to improve clinical outcome in mCPRC patients. Highlights: Pharmacokinetic study in mCRPC patients treated with abiraterone (ABI). ABI plasma trough concentration correlates with prostate-specific antigen response and progression-free survival. Role of ABI concentration monitoring for decision-making in progressive disease.